The consequences of micro-discretions and boundaries in the social prescribing link worker role in England: a realist evaluation - Stephanie Tierney; Debra Westlake; Geoffrey Wong; Amadea Turk; Steven Markham; Jordan Gorenberg; Joanne Reeve; Caroline Mitchell; Kerryn Husk; Sabi Redwood; Anthony Meacock; Catherine Pope; et al. (Health and Social Care Delivery Research)
Background Social prescribing addresses non-medical factors affecting health and well-being. Link workers are key to its delivery by connecting people to relevant support, often in the voluntary, community and social enterprise sector. Funding from the National Health Service means that link workers are becoming a common part of primary care in England. Objective To explore and understand the implementation of link workers in primary care in England. Design A realist evaluation addressed the question – When implementing link workers in primary care to sustain outcomes – what works, for whom, why and in what circumstances? Setting Link workers and staff associated with seven primary care sites across England. Methods Researchers spent 3 weeks with each link worker, going to meetings with them, watching them interact with patients, with healthcare staff and with voluntary, community and social enterprise organisations. In addition, interviews were conducted with 61 patients and 93 professionals (voluntary, community and social enterprise representatives and healthcare staff, including link workers). Follow-up interviews were conducted with 41 patients and with link workers 9–12 months later. Data were coded and developed into statements to identify how context around the link worker triggers mechanisms that lead to intended and unintended outcomes. Results We found that link workers exercise micro-discretions in their role – actions and advice-giving based on personal judgement of a situation, which may not always reflect explicit guidance or protocols. Our analysis highlighted that micro-discretions engender positive connections (with patients, healthcare staff, the voluntary, community and social enterprise sector) and promote buy-in to the link worker role in primary care. Micro-discretions supported delivery of person-centred care and enhanced job satisfaction. Data also highlighted that lack of boundaries could place link workers at risk of overstepping their remit. Limitations Our research focused on link workers attached to primary care; findings may not be applicable to those working in other settings. Data were collected around seven link worker cases, who were selected purposively for variation in terms of geographical spread and how/by whom link workers were employed. However, these link workers were predominately white females. Conclusions Enabling link workers to exercise micro-discretions allows for responsiveness to individual patient needs but can result in uncertainty and to link workers feeling overstretched. Future work Poor link worker retention may, in part, be associated with a lack of clarity around their role. Research to explore how this shapes intention to leave their job is being conducted by authors of this paper. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme as award number NIHR130247. Plain language summary Problems in life affecting people’s health and well-being cannot always be fixed with medication. For example, loneliness can lower people’s mood, or worries about money can cause them to feel anxious. Social prescribing link workers are employed to support individuals with these ‘non-medical’ issues. They listen to people to find out about them and their circumstances. They may connect them to community groups, organisations or services, or help them get advice about things like benefits or housing. Our study explored how link workers are being implemented in primary care in England. We studied seven link workers based in different parts of England. We spent 3 weeks with each link worker, observing them at their workplace. We also interviewed these link workers and people they worked with; this included 61 patients, 61 primary care staff, 5 other link workers and 20 individuals from the voluntary or community sector. We found big differences in what link workers did in their roles; in how long they saw patients for and how often, how many patients they were supporting at one time, their professional and personal backgrounds, whether they worked in a practice alone or were part of a bigger team of people delivering social prescribing. Link workers had varying levels of flexibility (or discretion) in their jobs; this allowed them to support patients’ individual needs. Such flexibility gave them job satisfaction as they were able to use their judgement about how to work with patients to provide person-centred support. However, if this went too far – and link workers had too few boundaries and not enough guidance – they ended up feeling overwhelmed by their job.